Neurodevelopmental disorders and microcephaly: how apoptosis, the cell cycle, tau and amyloid-β precursor protein APPly - Sokol, Deborah K.; Lahiri, Debomoy K. (Frontiers in Molecular Neuroscience, 2023)
Recent studies promote new interest in the intersectionality between autism spectrum disorder (ASD) and Alzheimer's Disease. We have reported high levels of Amyloid-β Precursor Protein (APP) and secreted APP-alpha (sAPP𝑎) and low levels of Aβ peptides 1-40 and 1-42 (Aβ40, Aβ42) in plasma and brain tissue from children with ASD. A higher incidence of microcephaly (head circumference less than the 3 rd percentile) associates with ASD compared to head size in individuals with typical development. The role of Aβ peptides as contributors to acquired microcephaly in ASD is proposed. Aβ may lead to microcephaly via disruption of neurogenesis, elongation of the G1/S cell cycle, and arrested cell cycle promoting apoptosis. As the APP gene exists on Chromosome 21, excess Aβ peptides occur in Trisomy 21-T21 (Down's Syndrome). Microcephaly and some forms of ASD associate with T21, and therefore potential mechanisms underlying these associations will be examined in this review. Aβ peptides' role in other neurodevelopmental disorders that feature ASD and acquired microcephaly are reviewed, including dup 15q11.2-q13, Angelman and Rett syndrome.